The Impact of Service Quality on Customer Satisfaction in Cameroon’s Mobile Telephony Sector - Ngambi, Marcel T.; Abamukong, Achu Armstrong (American Journal of Management, 2020)
The objective of this study is to investigate the relationship between service quality and satisfaction of mobile telephone users in Cameroon. Service quality was measured using eight constructs (Tangibility, Reliability, Responsiveness, Empathy, Assurance, Economy, Technical Quality and Image) while users ’satisfaction was captured through perceived performance, comparison standards and repurchase intentions. Data was collected from 386 Cameroonian mobile telephone users of the cities of Yaounde, Douala, Bamenda and Buea. We regressed measures of customer satisfaction on service quality variables. The main result of the study is that high service quality contributes significantly to higher customer satisfaction. The most influential service quality variables were image and economy while the least effective determinant of satisfaction was responsiveness. Based on these findings, we recommend mobile telecommunication operators to concentrate on improving their image and reputation to achieve higher customer satisfaction. Moreover, given the relatively high value of the variable “economy”, a low-price strategy is also encouraged while least attention should be directed to “responsiveness”.